Will Higher Industry Concentration Promote Food Safety - 余建宇 莫家颖 龚强 (China economist (Beijing, China), 2016)
Given the serious situation of food safety in China, the Chinese government has followed the policy of diverting resources to certain competitive firms and thus increasing market concentration as a means to improve food safety. This policy departs from the common practice in advanced economies of encouraging competition and restraining excessive corporate expansion. Based on the theoretical analysis framework of game theory, this paper investigates the impact of increased industry concentration on food safety. Our study finds that in a market environment where quality food enjoys a high premium, greater evenness of corporate size across firms will be conducive to mutual cooperation among firms for the provision of quality and safe food. Yet if the market is less sophisticated and the premium for quality food is low, it will be difficult to form mutual cooperation among firms and easier for low quality food manufacturers to take a free ride. In these circumstances, the larger size of quality food firms will make them less vulnerable to be affected by free rides and more motivated to manufacture quality and safe food. The latter scenario is consistent with China＇s market reality. Hence, increasing industry concentration in the current stage is conducive to mitigating the food safety crisis. Yet with the gradual improvement in market conditions, a competitive policy will be a better option in the long run.